Conflations of Correlation with Causation in Researchers' Descriptions of Their Work - Darling, Stephanie; Murray, Carly; Bleske-Rechek, April L.; Priebe, Mark; Gunseor, Michaela (My University, 2017)
The objective of this research is to determine the frequency with which social scientists use unjustified causal language in academic descriptions of their work.
Color poster with text, images, and charts.
Keywords: Mindware gap; Researchers; Posters; Correlation; Causation